Adapting Self-Regulated Strategy Development Model to Teach Deaf Learners English Writing Skills - Morai, Mamotjoka; Kawai, Norimune; Hayashida, Masashi; Shinkai, Akira; Matsumiya, Nagako (Angstrom Centre of Education, 2024)
Writing is a facet of learning and daily communication. However, many deaf and hard-of-hearing learners (DHHLs) struggle with writing despite teachers’ efforts to teach writing effectively. For decades, researchers have developed interventions and theories for improving writing instruction with limited implementation research to assess what works and what does not, for whom, where, and how. The international goal to achieve quality education through Sustainable Development Goal 4, with target 4.6 for improving literacy skills by 2030, has increased awareness of improving learners’ literacy skills in developing countries, including those with disabilities. However, there is limited research on evidence-based interventions in improving DHHLs’ literacy skills, particularly in writing. One of these interventions is the self-regulated strategy development model (SRSD). This study describes the implementation of SRSD in Lesotho with two Grade 6 DHHLs, specifically focusing on identifying the teacher’s instructional adaptations and learners’ development as writers during SRSD instruction. This study also considers the pedagogical implications of SRSD instruction when used with DHHLs with limited English backgrounds.